Advice-seeking and advice-giving in Arabic computer-mediated communication in the medical context - Al-Mutairi, Naif Barakah; Mahzari, Mohammad (Frontiers in Psychology, 2023)
The current study aims to examine the discourse patterns and strategies of advice-seeking and advice-giving through Arabic computer-mediated communication (CMC) in the medical context. The contribution of this study lies in examining and analyzing the discourse patterns of CMC between patients and doctors in Arabic, how these patterns help doctors understand the advice sought and inquiries made by their patients, and how they help patients understand the comments made by their doctors on their inquiries. The data consist of 300 messages categorized into 150 advice-seeking (postings) and 150 advice-response (replies) messages. They were manually collected from a public medical website by copying and pasting them into an Excel spreadsheet for coding and statistical analyses. Two models were used to analyze the speech acts of advice. Morrow’s model was used for advice-seeking, while Hinkel’s taxonomy was used for advice responses, after some modifications were made to both models. The findings revealed that advice-seeking and advice-response messages had three parts: opening, middle, and closing. The study revealed that both patients and doctors used the opening and closing parts occasionally, unlike the middle part, which was used more often. For advice-seeking, describing the medical problem was the most frequent strategy used by patients when they asked for advice, followed by yes/no questions. These types of strategies were used in advice-seeking more frequently than others. Additionally, it was found that asking yes/no questions and describing the medical problem was the most frequent compound strategy used by patients seeking advice. However, for advice responses, the results revealed that giving clarification/information was the most frequent strategy used by doctors, followed by direct advice. When compared with other types, these two types were used frequently in the advice responses. The results also demonstrated that giving clarification/information and direct advice was the most frequent compound strategy used by doctors in advice responses.